STRATEGI PENGELOLAAN PERPARKIRAN DI KOTA SALATIGA - Nita Haryanti; Hardi Warsono; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
City parking area Salatiga has function in parking management performing at Territotial Salatiga City. Pads goes upon this management number region regulation 12 year 2011 about Parking Management at Common Wayside. Until now, parking management performing is still there are some problem for example : prasarana’s medium facility that subtraced is equal to, society and executor behavior that doesn’t play the game and its reducing coordination of Observation and Operation section. The position of the Department of Transportation in parking management in Salatiga City is as an agency or agencies that manage parking management in Salatiga City, one of them in the implementation of regional development that will work well if one has a good strategy in the development of transportation facilities. Research Parking Management Strategies in Salatiga City using qualitative descriptive research method, in which this study describe, record, analyze, and interpret the conditions of Salatiga. The analysis process is conducted which begins with the identification of internal and external environment to assess weakness, strengths, opportunities, and threats in the increase in parking the city of Salatiga. Then proceed by using SWOT analysis, so that the resulting strategy SO, strategy ST, WO strategies, and strategies using the SWOT matrix WT. The next step is to identify strategic issues based on the results of a SWOT analysis using litmus tests to determine strategic alternatives, decide on a strategy for estimating the increase in parking retribution.